2007
DOI: 10.1158/1078-0432.ccr-07-0842
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Foxp3+ Regulatory T Cells Mediate Immunosuppression in Prostate Cancer

Abstract: Prostate cancer is the most common cancer among men in the United States and the second most common malignant cause of male deaths in the United States. There is currently no effective therapy for late-stage disease, whereas surgery or radiation therapy is the only choice for early-stage disease. Immunotherapy affords a promising approach to the treatment of various types of cancer, including prostate cancer (1 -5). Although peptide-or dendritic cell -based vaccines can induce antigenspecific immune responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
281
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(305 citation statements)
references
References 45 publications
16
281
0
8
Order By: Relevance
“…In our TRP-SIY model, effector CTLs rapidly become tolerant in antigen-expressing prostate tumors without being physically deleted. Kiniwa et al recently demonstrated the importance of CD8 ϩ Foxp3 ϩ suppressor cells in human prostate tumors (35). However, both intracellular staining and transcriptional profiling show that tolerized 2C cells in the TRP-SIY mice are not converted into Foxp3 ϩ suppressor cells (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…In our TRP-SIY model, effector CTLs rapidly become tolerant in antigen-expressing prostate tumors without being physically deleted. Kiniwa et al recently demonstrated the importance of CD8 ϩ Foxp3 ϩ suppressor cells in human prostate tumors (35). However, both intracellular staining and transcriptional profiling show that tolerized 2C cells in the TRP-SIY mice are not converted into Foxp3 ϩ suppressor cells (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…Siegmund et al describe this phenotype to be uniquely present in human tonsil tissue, 41 however their presence was also demonstrated in human prostate cancer. 42 Whether these T cells with tolerogenic phenotype are a reflection of suppressed local immunity or part of an ongoing adaptive immune response can not be concluded from this data.…”
Section: Discussionmentioning
confidence: 91%
“…The paper mentions the significance of immunological vigilance and the fact that CD8 Treg may promote tumoral growth. It also describes this cell subpopulation in patients with multiple sclerosis in whom lower numbers of these cells were correlated with relapse, a fact that may evidence their immunosuppressant role in the control of autoimmune diseases (Giovanni Frisullo, 2010;Chaput, 2009;Kiniwa, 2007). Recently described populations of CD8+ Treg include CD8+ IL-10+ cells present in ovarian carcinoma, which are induced by plasmocytoid dendritic cells infiltrating the tumor.…”
Section: Clinical Relevance Of Regulation and Induction Of Tolerance mentioning
confidence: 98%